THE RELEVANCE OF ULTRASONOGRAPHY TO THE CONCEPT OF IDDAH FROM THE PERSPECTIVE OF MAQASID AL-SHARIAH - Zainal Abidin , Ali; Saini (International Journal of Multidisciplinary Reseach, 2025)
This study discusses the relevance of using ultrasound technology (USG) to the concept of iddah in Islamic family law, employing a maqasid al-syariah approach. The background of this study stems from a social phenomenon where some women consider ultrasound results showing an empty womb to be grounds for waiving the obligation of iddah, sparking debate between medical authorities and Sharia norms. The objective of this study is to analyze classical fiqh perspectives on iddah, examine medical findings on the function of ultrasound, and evaluate both within the framework of maqasid al-syariah. The method employed is qualitative research using a literature review approach, drawing on the works of classical scholars, contemporary fiqh literature, and medical references related to ultrasound. Data were analyzed comparatively and normatively, taking into account the principles of maqasid al-syariah, particularly the aspects of hifz al-din (preserving religion) and hifz al-nasab (preserving lineage). The results of the study indicate that although ultrasound has accurate diagnostic functions in confirming the condition of the uterus, this technology cannot replace the sharia obligation to undergo the iddah period. This is because iddah is not merely intended to confirm the emptiness of the uterus, but also has dimensions of worship, social, and moral aspects, such as preserving lineage, providing space for mourning, and opening the possibility of reconciliation. Thus, the contribution of this research lies in emphasizing that the use of modern medical technology should be positioned as a supportive tool, not as a replacement for the normative provisions of Islamic law